Comparison of necrotizing enterocolitis (NEC)-related apoptosis factors between preterm and full-term rats - Hye-rim Lee; Dayoung Ko; Kyeung Yeup Lee; So young Kim; Joong Kee Youn; Hee Beom Yang; Hyun-Young Kim (Scientific Reports)
Abstract The aim of this study was to determine whether there is a difference in the degree of apoptosis and the pathways leading to necrotizing enterocolitis (NEC) between preterm and full-term rat pups. To achieve this goal, we investigated the pathogenesis of NEC. premature Sprague‒Dawley (SD) rat pups delivered by cesarean section at a gestational age of 21 days (preterm group), as well as full-term SD rat pups four days after birth (full-term group). The pups were exposed to lipopolysaccharides (LPS) and hypoxia to induce necrotizing enterocolitis. Both preterm and full-term rats developed necrotizing enterocolitis. The results indicated that the degree of apoptosis was greater in both the preterm and full-term NEC groups than in the untreated preterm and full-term control groups. Compared with the control group, the full-term group also presented a reduction in Bcl-2 levels and an increase in the ratio. Moreover, the preterm group presented significantly increased RIPK1 expression, suggesting the induction of RIPK1-dependent apoptosis. These findings suggest that the pathophysiology of necrotizing enterocolitis induced by LPS + hypoxia is associated with the programmed cell death pathway. It appears that the apoptotic pathway of the Bax/Bcl-2 system is the main mechanism of necrotizing enterocolitis in full-term rats. In contrast, several other mechanisms, including TNF-α-induced apoptosis mechanism, may work together for necrotizing enterocolitis in preterm rats. However, further studies are needed to elucidate the differences in the pathogenesis of necrotizing enterocolitis development between preterm and full-term rats.